Aspects of the Causative Morpheme -i- in Tonga (M64) - Khama Hang’ombe; Minyono Mwembe; Charton Siantumbu (Randwick International of Education and Linguistics Science Journal, 2020)
This paper examines the phonological behaviour of the causative morpheme –i- in Tonga, using the Plateau and Valley Tonga varieties. It identifies the various segments in radical final positions of different verbal forms and seeks to establish how the introduction of the causative morpheme in their environment affects the segments. The paper finds that in some cases the morpheme induces phonological change to the segments preceding the morpheme, with more phonological ‘activity’ noted in Plateau Tonga. The influence of the morpheme identified in the study is that it induces fricativisation, palatalisation, or glottalisation to radical final segments of the verbs where it is introduced, depending on the nature the concerned segment. The conclusion drawn in the paper is that the influence of the morpheme is more pronounced in Plateau Tonga than in Valley Tonga.